Exercise rapidly increases expression of the monocarboxylate transporters MCT1 and MCT4 in rat muscle - Coles, Lisa (Blackwell Science Inc, 2004)
We examined the effect of a single exercise session on the protein and mRNA expression of the monocarboxylate transporters MCT1 and MCT4 in rat soleus (SOL), and red (RG) and white gastrocnemius (WG) muscles. Muscle samples were obtained at rest before 2 h of treadmill exercise (21 m min(−1), 15% grade) and immediately after exercise, as well as 5, 10 and 24 h after exercise. During the 2 h exercise bout, MCT1 proteins in RG (+60%) and WG (+56%) were increased (P < 0.05). MCT1 protein was further increased thereafter, with peak increments occurring 10 h after exercise in RG (+157%), WG (+193%) and SOL (+179%) (P < 0.05). Twenty-four hours after exercise, MCT1 protein was still up-regulated in WG (+100%) and SOL (+55%) (P < 0.05), but not in RG. MCT1 mRNA was up-regulated during exercise in RG (+53%) and WG (+98%) and remained elevated until 24 h post-exercise in RG (P < 0.05), but in WG, MCT1 mRNA decreased transiently to pre-exercise levels at 5 and 10 h after exercise, before increasing again at 24 h (+150%) (P < 0.05). MCT4 protein and mRNA were not increased in WG muscle during and after exercise (P > 0.05). In contrast, during exercise, in RG (+41%) and SOL (+98%) MCT4 protein was increased (P < 0.05). Peak increases in MCT4 protein were observed 10 h after exercise in RG (+131%) and SOL (+323%) (P < 0.05). MCT4 protein was still up-regulated 24 h after exercise (RG: +106%; SOL +225%) (P < 0.05). MCT4 mRNA in RG was not increased until 10 (+132%) and 24 h after exercise (+55%) (P < 0.05). These studies have shown that MCT1 and 4 proteins are transiently up-regulated by a single bout of exercise, involving post-transcriptional and transcriptional mechanisms. Thus, MCT1 and MCT4 belong to a class of selected metabolic genes that are very rapidly up-regulated with an exercise stimulus.